2021
DOI: 10.3390/jmse9050510
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study on Seasonal Variation of Marine Biotoxins and Related Harmful Algae in Bivalve Mollusks Bred in Sardinia (Italy, W Mediterranean Sea) from 2015 to 2020 and Assessment of Potential Public Health Risks

Abstract: Annual and interannual dynamics of shellfish toxins and associated harmful algal species (HAS) were analyzed from 2015 to 2020 in Tortolì Lagoon (Sardinia, west Mediterranean Sea). Analysis of seasonal occurrence of different harmful algae, such as Dinophysis spp., Prorocentrum spp., Pseudo-nitzschia spp. and Alexandrium minutum, was performed. The species Dinophysis acuminata and Dinophysis sacculus were responsible for the accumulation of lipophilic toxins belonging to the okadaic acid group (OAs) and pecten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Finally, the DO acid was detected according to the Standard Operating Procedure AESAN, 2008. The description of the methods has been previously described in Mudadu et al , 2021 .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the DO acid was detected according to the Standard Operating Procedure AESAN, 2008. The description of the methods has been previously described in Mudadu et al , 2021 .…”
Section: Methodsmentioning
confidence: 99%
“…OA was also detected in Sardinia, Italy (Mudadu et al, 2021) and in the Thermaikos Gulf in Greece (Ciminiello et al, 2006;Reizopoulou et al, 2008) (Table 1). An important amount (1.1 µg g -1 meat) of OA was recorded in Mytilus galloprovincialis in the Northern Adriatic Sea (Ciminiello et al, 1997).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 95%
“…Dinophysis is also responsible for the production of pectenotoxins (PTXs) in the Mediterranean Sea. PTX-2 was recorded for the first time in France in 2005 in the oysters with a maximum of 22 µg Kg -1 and in mussels with a maximum of 26 µg kg -1 in Thau Lagoon (Amzil et al, 2007), as well as found in oysters in Sardinia (Italy) during 2019 (Mudadu et al, 2021) and in mussels in Catalonia (Spain) in 2012 (Garcia Altares et al, 2016). Belin et al (2021) revealed frequent detection of high levels of PTX2-seco-acid in various sites of shellfish aquaculture in the French Mediterranean lagoons.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
“…625 Synthesis of the proposed structures of bathymodiolamides A and B, originally isolated from the deep-sea hydrothermal vent mussel Bathymodiolus thermophilus, gave products that exhibited discrepancies in NMR data and in vitro cytotoxicity proles. 626 The seasonal and location variations of levels of cyclic imine toxins in northern Adriatic Sea mussels, oysters, scallops and edible ascidians, 627 gymnodimine A in Spanish molluscs, 628 lipophilic toxins in shellsh from SE China, 629 and Southern Gulf of California, 630 and okadaic acids and pectenotoxin-2 toxins and associated algal species in a lagoon in Sardinia, 631 have been reported. The distribution of other mollusc/bivalve…”
Section: Molluscsmentioning
confidence: 99%
“…The seasonal and location variations of levels of cyclic imine toxins in northern Adriatic Sea mussels, oysters, scallops and edible ascidians, 627 gymnodimine A in Spanish molluscs, 628 lipophilic toxins in shellfish from SE China, 629 and Southern Gulf of California, 630 and okadaic acids and pectenotoxin-2 toxins and associated algal species in a lagoon in Sardinia, 631 have been reported. The distribution of other mollusc/bivalve related toxins including tetrodotoxin in shellfish in southern England, 632 and Central and Northern Adriatic Sea, 633,634 and domoic acid in mussels (Turkey), 635 and bivalves (NW Spain), 636 have also been described.…”
Section: Molluscsmentioning
confidence: 99%